2015
DOI: 10.1371/journal.ppat.1004938
|View full text |Cite
|
Sign up to set email alerts
|

IRF-5-Mediated Inflammation Limits CD8+ T Cell Expansion by Inducing HIF-1α and Impairing Dendritic Cell Functions during Leishmania Infection

Abstract: Inflammation is known to be necessary for promoting, sustaining, and tuning CD8+ T cell responses. Following experimental Leishmania donovani infection, the inflammatory response is mainly induced by the transcription factor IRF-5. IRF-5 is responsible for the activation of several genes encoding key pro-inflammatory cytokines, such as IL-6 and TNF. Here, we investigate the role of IRF-5-mediated inflammation in regulating antigen-specific CD8+ T cell responses during L. donovani infection. Our data demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 92 publications
(121 reference statements)
3
85
1
1
Order By: Relevance
“…By contrast, in macrophages, HIF regulates M1 and M2 polarization, motility, bactericidal activity and tumour development 48,49 . In dendritic cells (DCs), HIF modulates survival, migration, antigen presentation, interferon synthesis and differentiation 50,51 . Similarly, in T cells, HIF is important for the regulation of not only survival and differentiation but also proliferation and antitumour capacity 33 .…”
Section: Hif Modulation Of Immune Cell Functionmentioning
confidence: 99%
“…By contrast, in macrophages, HIF regulates M1 and M2 polarization, motility, bactericidal activity and tumour development 48,49 . In dendritic cells (DCs), HIF modulates survival, migration, antigen presentation, interferon synthesis and differentiation 50,51 . Similarly, in T cells, HIF is important for the regulation of not only survival and differentiation but also proliferation and antitumour capacity 33 .…”
Section: Hif Modulation Of Immune Cell Functionmentioning
confidence: 99%
“…The treatment of cells with siHIF‐1α decreases the parasitic burden, indicating that expression of HIF1‐α improves intracellular parasite growth . The use of a conditional HIF‐1α knockout mice in DCs supports this idea . These mice had lower parasite burden in spleen, better CD8 + T cell response, increased production of IL‐12, but lower production of IL‐6 and TNF‐α by splenic DCs .…”
Section: The Key Role Of Mdscs During Bacterial Viral and Parasiticmentioning
confidence: 83%
“…We have recently shown, using an experimental model for VL, that L. donovani promoted the stabilization of HIF-1α in DC by generating a highly proinflammatory microenvironment [133].…”
Section: Hif-1α and Leishmaniamentioning
confidence: 99%
“…As expected, stabilization of HIF-1α had functional consequences on DCs as well. Indeed, analysis of T cell responses in mice with a targeted deletion of HIF-1α in CD11c + cells revealed that that HIF-1α upregulation impaired sustained IL-12 expression in splenic DCs and upregulated IL-10 expression [133]. This resulted in enhanced CD8 + T cell expansion, a higher frequency of effector CD8 + T cells, and significantly lower splenic parasite burden.…”
Section: Hif-1α and Leishmaniamentioning
confidence: 99%
See 1 more Smart Citation